The block diagram method for designing the particle swarm optimization algorithm - Baiquan, Lu; Gaiqin, Gao; Zeyu, Lu (Journal of global optimization, 2012)
In this paper, the block diagram method of the dispersed control system is proposed for designing or improving the normal particle swarm optimization algorithms (PSO), that is, it uses the Jury-test of the control theory to compare the block diagrams getting from existing particle swarm optimization methods and finds out some defects of the existing particle swarm optimization methods, for example, the premature convergence of PSO algorithm, and so on. Thus a new particle swarm algorithm is also proposed for improving these defects, that is, the speed iteration and position iteration formulas of PSO are revised for both adjusting its convergence speed and jumping out of the local minimum points. To show effectiveness of the proposed method, the simulations of 13 benchmark examples are carried out, as a result, it indicates that the proposed method is very useful.